Turkey's Hegemonic Legacies and EU Accession Bid - Troulis, Markos (Budapest International Research and Critics University, 2019)
The current paper focuses on Turkey’s EU accession bid in the light of Ahmet Davutoğlu’s thoughts for her positioning in the peripheral and the international systems. The importance of analyzing the former Prime Minister’s thoughts and methodology is high for anybody to understand Turkey’s strategic aims and their consequences for the systemic stability mainly on the regional level. Moreover, the afore-mentioned debate refers to the problematique of the future of the EU, the transformation of its nature and the core issues surrounding the post-war stability in Europe, since Turkey is a candidate country for EU accession. In other words, the nature of Ahmet Davutoğlu’s foreign policy priorities and practices is described in parallel with the substance of the cosmotheoretical values having led Europe to a relatively peaceful post-war coexistence of its nations.